An Experimental Investigation on the Dynamic Response of Buried RC Pipes Induced by Falling Impact - Yingkang Yao; Nan Jiang; Guopeng Lyu; Jinshan Sun; Feng Yang (Sensors, 2024)
Unexpected ground impacts can seriously affect the stability and operational safety of buried pipelines. In this paper, a full-scale modeling test of the dynamic response of a buried concrete pipeline under falling rock impact based on dynamic sensor testing was conducted. A commercially available reinforced concrete pipeline, buried in a clayey soil site, was used, and a 50 kg concrete ball was used to investigate the impact above the pipeline. Considering the purpose of the test, the falling process of the concrete ball and the surface vibration velocity induced by the touchdown of the concrete ball were monitored using a high-speed camera and a vibration signal tester, respectively. The dynamic response signals of the pipe under surface impact were tested using strain gauges and earth pressure gauges combined with dynamic sensors such as dynamic signal tester, and the dynamic response law was analyzed. The experimental results will provide a basis for the design of the impact resistance of reinforced concrete pipes.